(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
All humans have one thing in common, namely listening, speaking, and the ease of communicating with one another. For those who hearing loss, they do not have access to learning information media such as physical education and sports learning at special schools. Related communication barriers, Deaf students limited access to competitive experiences. The communication model is one of the important factors in learning physical education and sport for Deaf students. The purpose of this study was to analysis the communication model of learning physical education and sport for Deaf students in Special Schools, Special Region of Yogyakarta. This research method uses a survey. The technique of collecting data using a survey with a questionnaire technique and sent electronically, google form. Data analysis used quantitative descriptive analysis. The results of this study showed that the communication model used was 60.7% of respondents who responded the highest by using verbal communication (oral) and also by using manual communication (gesture) to communicate. The instructional media used to teach, shows that the teacher uses a pilot for Deaf students 75%. The causes of communication barriers 57.1% indicate students misunderstood the meaning of the message. Physical education and sport teachers in the learning process for Deaf students use more verbal communication (oral) and the pilot exercise formula results in Deaf students misunderstanding in capturing messages from the teacher. Teachers need to develop language and cultural awareness which is the identity of the Deaf individual.